Distribusi Topik Skripsi Mahasiswa Berbasis Android Dengan Mekanisme Publish/Subscribe Di FILKOM Universitas Brawijaya - Gibran Haq; Rakhmadhany Primananda; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In the undergraduate program to take the final exam, a student is assigned to make the final task in the form of a thesis. In making this thesis a student first determine the topic to find the problem to be lifted. Problems that exist, final year students still difficult to determine the topic of thesis in the final project. Therefore some lecturers provide certain kinds of topics according to their field of expertise which are then published on the website. That way the student must often visit the website to see the latest topics that have been published by lecturers. And students also have to search for topics one by one according to the topic he wants. This is not efficient enough if students should frequently visit the website and search for topics one by one according to the topic to be discussed considering not knowing the time of publication of the latest thesis topic and not classified topic of thesis based on topic. With the mobile app using the Publish / Subscribe method the student will be more efficient in getting the latest thesis topic information and according to the desired topic. Based on the results of functional and non functional tests concluded to run as expected. Results from functional testing with 100% validation rate. While the result of non-functional testing is the time required to send messages from publisher to subscriber using QoS 0, QoS 1, QoS 2 is 0.490 seconds , 0.561 seconds, 0.720 seconds.